Applications of Tissue Decellularization Techniques in Ventricular Myocardial Biofabrication - Krishnan, Aravind; Wang, Hanjay; MacArthur, John Ward (Frontiers in Bioengineering and Biotechnology, 2022)
Ischemic heart disease is the leading cause of death around the world, and though the advent of coronary revascularization has revolutionized its treatment, many patients who sustain ischemic injury to the heart will go on to develop heart failure. Biofabrication of ventricular myocardium for replacement of irreversibly damaged ischemic myocardium is sought after as a potential therapy for ischemic heart failure, though challenges in reliably producing this biomaterial have limited its clinical application. One method that shows promise for generation of functional myocardium is the use of tissue decellularization to serve as a scaffold for biofabrication. This review outlines the methods, materials, challenges, and prospects of tissue decellularization techniques for ventricular myocardium biofabrication. Decellularization aims to preserve the architecture and composition of the extracellular matrix of the tissue it is applied to, allowing for the subsequent implantation of stem cells of the desired cell type. Decellularization can be achieved with multiple reagents, most of which have detergent properties. A variety of cell types can be implanted in the resulting scaffold, including cardiac progenitor cells, and embryonic or induced pluripotent stem cells to generate a range of tissue, from patches to beating myocardium. The future of this biofabrication method will likely emphasize patient specific tissue engineering to generate complex 3-dimensional constructs that can replace dysfunctional cardiac structures.